Humidity effect on pressure-velocity sensor examined in sound absorption measurement with ensemble averaging technique - Otsuru, Toru; Asniawaty, Kusno; Tomiku, Reiji; Okuzuno, Takeshi; Okamoto, Noriko; Che Din, Nazli (2013)
The authors have proposed an absorption measurement method (Ea-method) that utilizes ensemble averaging and pressure-velocity sensor (pu- sensor) for measuring surface normal impedance required for wave-based 1'00111 acoustics simulations. However, through some amount of measurements with pu-sensors, the authors have come to have a question about the effect of humidity to the stability of pu-sensor. Then, employing two pu-sensors with the same specifications, the authors conducted a series of experiment, at four periods from 2010 to 2011. One experiment consists both a pu-sensor calibration and an EA-method measurement. In each calibration or EA-method measurement, relative humidity around pu-sensor was systematically controlled from 35% to 60% with 5% step, and both temperature and atmospheric pressure were monitored. By comparing the standard deviations of resulting absorption coefficients, the authors examined the effect of the relative humidity difference between at the calibration and at the EA-method measurement to resulting absorption coefficient. Final results showed that the standard deviation of absorption coefficient increases as the difference of relative humidity increases. If the difference is kept closer to 0%, the standard deviation of measured absorption coefficient stays smaller,